Epigenetic Agents Trigger the Production of Bioactive Nucleoside Derivatives and Bisabolane Sesquiterpenes From the Marine-Derived Fungus Aspergillus versicolor - Wu, Jing-Shuai; Yao, Guang-Shan; Shi, Xiao-Hui; Rehman, Saif Ur; Xu, Ying; Fu, Xiu-Mei; Zhang, Xiu-Li; Liu, Yang; Wang, Chang-Yun (Frontiers in Microbiology, 2020)
Epigenetic agents, histone deacetylase inhibitor (SAHA) and DNA methyltransferase inhibitor (5-Aza), were added to Czapek-Dox medium to trigger the chemical diversity of marine-derived fungus Aspergillus versicolor XS-20090066. By HPLC and 1H NMR analysis, the diversity of fungal secondary metabolites was significantly increased compared with the control. With the aid of MS/MS-based molecular networking, two new nucleoside derivatives, kipukasins K (1) and L (2) were obtained. Meanwhile, the yields of four known nucleoside derivatives were significantly enhanced. In addition, one new bisabolane sesquiterpene, aspergillusene E (7), along with ten known derivatives were also isolated. The structures were elucidated by comprehensive spectroscopic methods of NMR and HRESIMS analysis. Compounds 1 and 7 displayed antibacterial activities against Staphylococcus epidermidis and S. aureus with the MIC values of 8–16 μg/mL. Our study revealed that the fungus A. versicolor XS-20090066 has been effectively induced by chemical epigenetic manipulation with a combination of SAHA and 5-Aza to produce new metabolites.